Penerapan Psak No. 45 Pada Yayasan Mandiri Anak Bangsa Nusantara Dalam Kaitannya Dengan Kualitas Informasi Pelaporan Keuangan. - Hasibuan, David (STIE Kesatuan, 2010)
A Foundation can be said as an organization established not to get just profit (non-profit) although in its progress the foundation needs a lot of fund earned from business activity. It means that the business activity is merely to provide fund, not as a major activity of the foundation. Therefore, itâs needed supervision on the foundation which can be done together with the community as stakehorders. Hence, financial transparency in the form of financial statement publication to public must be one of the arranged obligations. PSAK No. 45 which regulate the financial statement of non-profit organization has the same spirit, that is financial transparency of the organization requires consistent recording and reporting standard and it can be compared with PSAK. Itâs expected that the organization will be able to manage financial information more professionally and the information yielded has more quality. The main purpose of financial statement is to provide relevant information to fulfill the interest of the contributors or funders, organization members, creditors, and other sides who provide sources for the non-profit organization. The other purposes are to evaluate the services given by the non-profit organization and its capability to provide the services continuously and how the managers carry out their responsibility or perform. The result of the research done by the author shows that Yayasan Mandiri Anak Bangsa Nusantara has not yet presented financial statement in accordance with PSAK No. 45 that regulatethe financial statement of non-profit organization, in this case is the foundation. In the way to present the report, the foundation still provide it as a commercial organization reporting in general, that is just as balance of finance and profit-loss reporting. Concerning the information quality of the foundationâs financial statement, the foundation should provide its financial statement in accordance with PSAK No. 45. By applicating PSAK No. 45, the financial statement made by the foundation has financial information quality because it has met the requirements of cost effectiveness, relevance, and reliability.